Peranan Pajak Dan Seigniorage Terhadap Ketahanan Fiskal - Tahwin, Muhammad (STIE YPPI Rembang, 2008)
Abstract Success of the economic development is influenced by fiscal and monetary management with their regulations. Fiscal role is carried out in two basic corridors,Â Â fiscal consolidation which is carried out by controlling budget deficit, and strategy of budget funding which is intended to decrease the burden and risk of the government debt. This fact shows that fiscal and monetary policies in Indonesia is not carried out in a good harmony and synchronization. So, increasing of fiscal and monetary policies coordination is needed by synchronizing policies goal to stabilize monetary sectors. The source of government income which derives from tax or seigniorage has important role to increase fiscal endurance. So, it is important for the government to synchronize fiscal and monetary policies by equalizing the increasing of tax and price level.Key Words : Tax, Seigniorage